1999
DOI: 10.1086/300839
|View full text |Cite
|
Sign up to set email alerts
|

A Robust Classification of Galaxy Spectra: Dealing with Noisy and Incomplete Data

Abstract: Over the next few years new spectroscopic surveys (from the optical surveys of the Sloan Digital Sky Survey and the 2 degree Field survey through to space-based ultraviolet satellites such as GALEX) will provide the opportunity and challenge of understanding how galaxies of different spectral type evolve with redshift. Techniques have been developed to classify galaxies based on their continuum and line spectra. Some of the most promising of these have used the Karhunen and Loéve transform (or Principal Compon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
101
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(101 citation statements)
references
References 15 publications
0
101
0
Order By: Relevance
“…Panel a shows the histogram of the galaxy spectral classification parameter eClass as provided by the SDSS for DR1. This spectral classification parameter is based on a principal component analysis method (Connolly et al 1995;Connolly & Szalay 1999). Note that the spectral classification of galaxies by Connolly et al (1995) is slightly different from the one used in SS99 who removed from the analysis the wavelength regions containing emission lines.…”
Section: Overall Properties Of Our Sample Of Normal Galaxiesmentioning
confidence: 99%
“…Panel a shows the histogram of the galaxy spectral classification parameter eClass as provided by the SDSS for DR1. This spectral classification parameter is based on a principal component analysis method (Connolly et al 1995;Connolly & Szalay 1999). Note that the spectral classification of galaxies by Connolly et al (1995) is slightly different from the one used in SS99 who removed from the analysis the wavelength regions containing emission lines.…”
Section: Overall Properties Of Our Sample Of Normal Galaxiesmentioning
confidence: 99%
“…The treatment of incomplete data in PCA has already been discussed in the literature, e.g., Everson & Sirovich (1995) and Connolly & Szalay (1999). However, the implementation is complicated and deserves further discussion.…”
Section: Dealing With Incomplete Data In the Pcamentioning
confidence: 99%
“…It can be shown that the latter issue has a relatively straightforward, clean solution involving decorrelating the eigenspectra (which are not orthogonal when we do not use their entire wavelength coverage). This has been presented in Connolly & Szalay (1999). However, estimating the eigenspectra in the first place is much more difficult to address.…”
Section: Dealing With Incomplete Data In the Pcamentioning
confidence: 99%
See 1 more Smart Citation
“…The first method attempted was based on a PCA of spectroscopic objects using the method of Connolly & Szalay (1999). The spectral classification coefficient is generally calculated by using two out of five eigencoefficients that build up the expansion of the eigentemplates of a galaxy's spectrum.…”
Section: Morphology Classificationmentioning
confidence: 99%